Leadership Role in Managing Knowledge to Support Operational Performance - Mohamad Irsan Febrian; Anggara Wisesa (Jurnal Locus Penelitian dan Pengabdian, 2026)
Inter-shift operational performance variation persists in many mature World Class Manufacturing (WCM) environments, even when technical conditions are held constant across shift groups. However, the organizational mechanisms underlying this variation remain underexplored. This study addressed this gap by examining how shop-floor leadership behaviors shape knowledge management (KM) capabilities and processes in an FMCG bar soap department where three shifts operated with identical equipment, standards, and WCM tools but demonstrated persistent differences in Overall Equipment Effectiveness (OEE). A qualitative single-case study design was adopted, based on ten semi-structured interviews with shop-floor leaders and personnel across all three shifts. The data were analyzed using inductive thematic analysis. The analysis generated thirteen themes, which were synthesized into a dual-perspective account of leader-mediated and peer-mediated knowledge dynamics. A cross-shift analysis linked each shift’s leadership profile to its observed performance trajectory. Leadership behavior emerged as a key organizational condition that activated or constrained KM capabilities, even when WCM infrastructure was nominally identical, through two interconnected pathways: a cognitive pathway, in which leadership shaped developmental opportunities that strengthened realized absorptive capacity, and a relational pathway, in which leadership presence, support, and psychological safety influenced whether tacit knowledge was shared and internalized. The study reconceptualized KM capability as an activation-dependent rather than infrastructure-dependent construct and demonstrated that the Socialization, Externalization, Combination, and Internalization (SECI) model’s socialization and externalization modes were particularly prominent in mature shop-floor environments.